Proteomic analysis of candidate prognostic urinary marker for cervical cancer - Paitoon Aobchey (2018)
Urinary proteins are an important component in urine samples that can be used as biological indicators for clinical diagnosis of diseases, such as proteinuria, kidney failure, diseases in the bladder, urinary tract and related organs. In this present work, we investigated candidate protein biomarkers in urine for diagnosis of cervical cancer using proteomic approach. The urine samples were concentrated and de-salted through ultrafiltration (3 kDa), followed by Spin-50 mini-sephadex column and were then separated by two-dimensional electrophoresis (2-DE) and annotated by mass spectrometer. Comparing 2-DE results between individual healthy donors and cervical cancer, patients showed that 4 urinary proteins; Protocadherin-8, Aryl hydrocarbon receptor nuclear translocatorlike protein 2, Serum albumin and Endorepellin, C-terminal domain V of perlecan were overexpressed by two-fold in the patient samples. Only the endorepellin LG3 fragment was validated by Western blot analysis. We also used 2D Western blot and nano LC-MS/MS to confirm the urinary biomarker as endorepellin LG3 fragment. Our study suggests that proteomics approach may be useful for the study of urinary proteins and provides an opportunity to discovery aberrant protein-associated diseases. We also revealed the candidate biomarkers that may be applied for cervical cancer diagnosis which benefits for medical treatment. © 2013 Aobchey P, et al.